SYNTHESIS AND CHARACTERISTICS OF POLY(PARA-PHENYLENEVINYLENE) - Pham Thi Minh Chau; Jung Il Jin (ASEAN Journal on Science and Technology for Development, 2007)
Poly(para-phenylenevinylene) [PPV] films and nanotubes were prepared via chemical vapor deposition polymerization (CVDP) by vapor phase pyrolysis of ?, ?'-dichloro p-xylene on the quartz plate, silicon wafers and Al2O3 membrane substrate with the pore size f = 100 nm. We prepared graphitic carbon films and carbon nanotubes by carbonizing the poly(para-phenylenevinylene) [PPV] films and nano parterns under thermal treatment range from 500°C to 900°C. When the PPV films on quartz plate were treated at 900°C highly oriented graphitic carbon films were obtained. The characterization of the PPV nanotube and nanotube carbon has been investigated by means of IR, SEM, AFM and Raman scattering study.